Kesantunan Berbahasa Minangkabau dalam Tindak Tutur Menyuruh di Kenagarian Tambang Kecamatan IV Jurai Kabupaten Pesisir Selatan - Sukma, Fiky Reustia; Agustina, Agustina; Ngusman, Ngusman (Universitas Negeri Padang, 2012)
This article written to describethe usage of speech strategies, the context of speech act strategy, andthe effect of using speak to the politeness of Minangkabau language in speech act at Kenagarian Tambang Kecamatan IV Jurai Kabupaten Pesisir Selatan. This data of research command the are speech event and the research of people views about manner or unmanner the spoken. The source of data is people speaker at Kenagarian Tambang Kecamatan IV Jurai Kabupaten Pesisir Selatan. Data was collected using methods observe, technical record, and technical notes. These following of finding research.(1) The strategy that often in speech actÂ command of speech directly without any reason, (2) The context often used in speech act is the lower hearer, familiar, and the speech done for two people, (3) speech act strategy which is used by the society at Kenagarian Tambang Kecamatan IV Jurai Kabupaten Pesisir Selatan in command utterance giving a polite effect.